DAMPAK PEMEKARAN DESA TERHADAP KESATUAN HUKUM ADAT (STUDI KASUS PEMEKARAN DESA SIBIRUANG MENJADI DESA BANDUR PICAK KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR) - Helmi, Ahmad Zuhdi; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Governance Management mounted by Countryside of Bandur Picak of District of Koto of Pate;Upstream Camphor generate various polemic in management of countryside governance, specially Countryside of Bandur Picak, where countryside management during the time namely countryside of mains of Countryside Sibiruang cannot be locked out of a concept